FRUGAL LIVING LIFESTYLE AND DIGITAL MARKETING ON SAVING INTEREST: ISLAMIC CONSUMPTION ETHICS' PERSPECTIVE - Dzakirah, Nadiva Fahriyyah Ayu; Meldona, Meldona; Julaiha, Umi (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study analyzes the influence of frugal living and digital marketing on students' saving interest, with Islamic consumption ethics as the evaluative framework. The research uses a qualitative approach with a case study design, and data were collected through interviews with students from several Islamic universities in Malang City. The findings reveal that frugal living helps students manage their finances, limit spending, and increase their tendency to save. However, the strong influence of digital marketing often leads to impulsive buying behavior, which disrupts saving intentions. While most students are familiar with Islamic ethical concepts such as zuhud , israf , and tabdzir , these values are not yet fully internalized in their consumption habits. The study concludes that integrating frugal living with Islamic consumption ethics can effectively overcome digital consumerism challenges and promote a saving culture among young people.